Karakter Morfologi Bunga Dan Buah Putat (Barringtonia acutangula (L.) Gaertn.): Morphological Characteristics of Putat Flowers and Fruit (Barringtonia acutangula (L.) Gaertn.) - Dewi, Syntiya; Hariyadi, Bambang; Ihsan, Mahya (Biospecies, 2023)
This research delves into the morphological characteristics of Putat (Barringtonia acutangula (L.) Gaertn.) in its natural habitat at Tangkas Lake, Muaro Jambi Regency, Jambi Province. In a landscape where water levels ebb and flow, Putat predominantly swathes the lake, enriching its visual allure and nurturing the area's development into a tourist attraction. The captivating aesthetics of Putat, marked by its distinct and briefly blossoming flowers, enhance the lake's appeal, drawing community interest and tourism. The study is meticulous, utilizing purposive sampling at two strategic locations and employing descriptive analysis supported by visual representations and tables. The findings unveil detailed insights into the plant’s flowers, fruits, and seeds. Putat’s flowers are found to be vibrant, unlimited compound entities, while its fruit evolves from a verdant to a purplish hue upon maturity, encompassing a singular, resilient seed. This in-depth exploration contributes valuable knowledge to the limited existing information, facilitating a deeper understanding of Putat’s unique ecological presence and biodiversity at Tangkas Lake. Keywords: Barringtonia acutangula, Putat, Danau Tangkas, Flower, Morphological character   Abstrak Penelitian ini mengkaji Putat (Barringtonia acutangula (L.) Gaertn.) di habotat alaminya di Danau Tangkas, Kabupaten Muaro Jambi, Provinsi Jambi. Putat yang tumbuh alami di danau memperkaya ekosistem lokal dengan keindahan flora uniknya, dan meningkatkan potensi danau sebagai destinasi wisata. Kajian ini berfokus pada karakterisasi morfologi bunga, buah, dan biji putat, untuk mengisi kekurangan informasi mengenai proses reproduksi tumbuhan ini. Data dikumpulkan menggunakan metode sampling purposif dilanjutkan dengan analisis secara deskriptif. Hasil penelitian menunjukkan bunga putat sebagai bunga majemuk tak terbatas dengan corolla merah yang menarik, dan struktur yang kompleks. Buah putat, berbentuk lonjong dan berkembang dari hijau menjadi hijau keunguan saat matang, serta mengandung biji tunggal yang kokoh. Temuan ini memberikan kontribusi penting dalam pemahaman lebih lanjut mengenai biodiversitas dan adaptasi ekologi Putat di habitatnya. Kata kunci: Barringtonia acutangula, Putat, Danau Tangkas, Bunga, Morfologi